“Chess” Educational Subject In Elementary School - Dallakyan, Armine; Martirosyan, Naira; Asatryan, Zaruhi (Զանգակ հրատ.)
The article analyzes the peculiarities of teaching chess in elementary school. The Republic of Armenia is moving to ability-based learning with the new standard requirements for education. The educational subject “Chess” has an excellent potential for forming personal qualities and developing the creativity and abilities of a junior high school student who faces the challenges of modern life, analyzes, synthesizes, summarizes, thinks critically, and initiates. The problem of studying the professional competencies of the elementary school "Chess" teacher is urgent and topical due to: ✓ Non-standardized requirements, competency-based learning (Procedure for formation and approval of the State Standard of General Education,2021). ✓ with the ever-increasing demands of the labour market in training a specialist, ✓ with personality formation problems of younger schoolchildren. The components of the professional competence of the elementary school chess teacher have also been developed and presented in the article.
Keywords: Education